An Explanatory Sequential Study on Adverse Childhood Experiences and Failed Relationships - Eula Pauline S. Mackay; Micaela Lyra Evangelista; Jade I. Hernandez; Angelica T. Hufana; Neo H. Lanceta; Andrie Jann V. Akilith (Research Synergy Foundation Press, 2026)
Emerging adulthood is a critical developmental stage marked by identity exploration, emotional regulation, and the formation of intimate romantic relationships, which have lasting implications for psychological well-being and relational stability. Individuals exposed to Adverse Childhood Experiences (ACEs), including abuse, neglect, and household dysfunction, may face greater difficulty maintaining healthy romantic relationships due to disrupted attachment, emotional processing, and coping mechanisms associated with toxic stress. Grounded in Attachment Theory and the Vulnerability–Stress–Adaptation Model, this study examined the relationship between ACEs and failed romantic relationships among 115 emerging adults using an explanatory sequential mixed-methods design. Quantitative results showed that most participants (74.8%) reported one to two failed romantic relationships, while only 5.2% reported five to six failures, suggesting limited yet meaningful relational instability. ACE-Q classifications indicated that 42.61% of participants were intermediate risk and 41.74% high risk, with 84.35% of the sample exposed to elevated toxic stress. Biserial correlation analysis revealed a statistically significant small-to-moderate positive association between ACE scores and the number of failed relationships (r = .249, p = .009), indicating that higher childhood adversity was modestly linked to increased relationship failure. To contextualize these findings, qualitative interviews were conducted with seven participants reporting high ACE scores and multiple failed relationships. Thematic analysis identified five core themes: trust dynamics, emotional expression, emotional patterns, emotional coping, and coping support. Overall, the findings suggest that although ACEs contribute to relational vulnerability among Filipino emerging adults, trauma-informed support, strong social networks, and adaptive emotional coping strategies may mitigate risks and promote healthier romantic relationships.